2015
DOI: 10.1093/cid/civ519
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal Seroepidemiology 1 Year After the PsA-TT Mass Immunization Campaign in Burkina Faso

Abstract: Background. A group A meningococcal (MenA) conjugate vaccine, PsA-TT (MenAfriVac), was introduced in Burkina Faso via mass campaigns between September and December 2010, targeting the 1- to 29-year-old population. This study describes specific antibody titers in the general population 11 months later and compares them to preintroduction data obtained during 2008 using the same protocol.Methods. During October–November 2011, we recruited a representative sample of the population of urban Bobo-Dioulasso aged 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…[ 23 , 24 ] However, some studies suggest that SBA titers against the vaccine reference strain may not correlate with clinical protection against other NmA strains, and alternate serologic indicators of vaccine-induced immunity may be needed. [ 31 , 32 ] If vaccine-strain SBA does not cross-protect against other strains, VE could decrease over time as new NmA strains emerge. To allow for this possibility, we repeated all analyses with the Updated Vaccination-Plus model assuming fast waning from the Vaccinated state (mean duration of protection, 4.6 years).…”
Section: Methodsmentioning
confidence: 99%
“…[ 23 , 24 ] However, some studies suggest that SBA titers against the vaccine reference strain may not correlate with clinical protection against other NmA strains, and alternate serologic indicators of vaccine-induced immunity may be needed. [ 31 , 32 ] If vaccine-strain SBA does not cross-protect against other strains, VE could decrease over time as new NmA strains emerge. To allow for this possibility, we repeated all analyses with the Updated Vaccination-Plus model assuming fast waning from the Vaccinated state (mean duration of protection, 4.6 years).…”
Section: Methodsmentioning
confidence: 99%
“…SIAs: Twelve studies reported vaccination coverage for SIAs. Three studies reported coverage data on meningococcal serogroup A (PsA-TT) vaccine 29 , 30 , 44 , five on measles vaccine 31 , 32 , 34 , 56 , 57 and two on yellow fever vaccine 36 , 43 . Each of the remaining two studies reported on one vaccine; cholera 38 and meningococcal bivalent polysaccharide A/C vaccine 46 .…”
Section: Resultsmentioning
confidence: 99%
“…4 Davycas International, Ouagadougou, Burkina Faso. 5 Ministère de la Santé, Ouagadougou, Burkina Faso. 6 UNICEF, New York, NY 10017, USA.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Infected persons usually experience sudden onset of high fever, neck stiffness, confusion, nausea, and vomiting; about half will die without prompt medical treatment [4]. To help reduce the meningococcal meningitis burden in endemic African countries, meningococcal serogroup A conjugate vaccine (MACV, MenAfriVac™) was introduced beginning in 2010 through mass vaccination campaigns for people from age 1 to 29 years [5]. The incidence of serogroup A meningitis declined sharply following MACV mass vaccination campaigns in these countries, including Burkina Faso [6].…”
Section: Introductionmentioning
confidence: 99%